Lichen sclerosus associated with Turner syndrome treated with photodynamic therapy: A case report - Yukun Wang; Jie Liu (Photodiagnosis and Photodynamic Therapy)
Turner syndrome (TS) is a rare clinical condition associated with a completely or partially absence, or structural abnormality of an X chromosome, mainly representing as short stature and skeletal anomalies, female hypergonadotropic hypogonadism and infertility. Skin is frequently involved in TS, especially autoimmune diseases like vitiligo and lichen sclerosus (LS).Here, we present a 10-year-old Chinese girl with TS combined with both vulvar LS (VLS) and extragenital LS, who had been misdiagnosed as eczema and vitiligo for years. In order to control LS sufficiently and allay the parents’ concerns of potential side effects of topical corticosteroids, she was prescribed with tacrolimus ointment on the extragenital lesions, and photodynamic therapy (PDT) for vulvar lesions. For PDT regimen, we used 5-aminolevulinic acid (ALA) as photosensitizer and 633 nm red light to irradiate the lesion area at 60 mW / cm2 for 30 min each time. After 6 times of treatment at 2-week intervals, a satisfactory remission of both pruritus and lesion severity was achieved.So far, the guideline on TS did not include LS as a common comorbidity to raise attention. However, accurate diagnosis and effective treatment are essential for LS to avoid the possibilities of developing labial atrophy, adhesion, or even vulvar cancer. Based on our research, PDT can significantly relieve subjective symptoms, objective lesion severity and histopathological changes of VLS with good tolerance, and therefore can also be a safe and effective therapeutic alternative in such comorbidity in TS patients.